A perfect islet: reviewing recent protocol developments and proposing strategies for stem cell derived functional pancreatic islets - Sujitha Sali; Leen Azzam; Taraf Jaro; Ahmed Ali Gebril Ali; Ali Mardini; Omar Al-Dajani; Shahryar Khattak; Alexandra E. Butler; Juberiya M. Azeez; Manjula Nandakumar (Stem Cell Research & Therapy)
Abstract The search for an effective cell replacement therapy for diabetes has driven the development of “perfect” pancreatic islets from human pluripotent stem cells (hPSCs). These hPSC-derived pancreatic islet-like β cells can overcome the limitations for disease modelling, drug development and transplantation therapies in diabetes. Nevertheless, challenges remain in generating fully functional and mature β cells from hPSCs. This review underscores the significant efforts made by researchers to optimize various differentiation protocols aimed at enhancing the efficiency and quality of hPSC-derived pancreatic islets and proposes methods for their improvement. By emulating the natural developmental processes of pancreatic embryogenesis, specific growth factors, signaling molecules and culture conditions are employed to guide hPSCs towards the formation of mature β cells capable of secreting insulin in response to glucose. However, the efficiency of these protocols varies greatly among different human embryonic stem cell (hESC) and induced pluripotent stem cell (hiPSC) lines. This variability poses a particular challenge for generating patient-specific β cells. Despite recent advancements, the ultimate goal remains to develop a highly efficient directed differentiation protocol that is applicable across all genetic backgrounds of hPSCs. Although progress has been made, further research is required to optimize the protocols and characterization methods that could ensure the safety and efficacy of hPSC-derived pancreatic islets before they can be utilized in clinical settings.